PENGARUH MEDIA PEMBELAJARAN BANGUN DATAR BERBASIS ULAR TANGGA TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VI SD NEGERI SINDANGSARI III - Noviantik, Dicha; Zuliani , Rizki; Eka Saputri , Rahmawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to determine the effect of snakes and ladders-based learning media on flat figures on the mathematics learning outcomes of class VI students at SD Negeri Sindangsari III who have difficulty learning mathematics using verbalism. The research was conducted in 2023-2024. This research method uses quantitative data collection techniques in the form of observation, tests and documentation. The sample used in this research was 30 students taken from a population of 60 students. A total of 30 students were given instruction using snake and ladder-based flat building media. And after being given teaching using flat building media tools based on snakes and ladders. Then it is measured using repetition. From the repetition before using snakes and ladders-based flat shapes and after being given using snakes and ladders-based flat shapes then analyzed using product moment correlation and with a significance level of 0.05. Based on the research results of normality and homogeneity tests carried out by the r test and t test, what was obtained was rcount was greater than rtable and tcount was greater than ttable, which means the alternative hypothesis was accepted and the null hypothesis was rejected. Thus, it can be concluded that mathematics learning outcomes for students who have difficulty learning mathematics verbally can be improved by using flat building media tools based on snakes and ladders.